2018
DOI: 10.1007/s10867-018-9499-2
|View full text |Cite
|
Sign up to set email alerts
|

Is a constant low-entropy process at the root of glycolytic oscillations?

Abstract: We measured temporal oscillations in thermodynamic variables such as temperature, heat flux, and cellular volume in suspensions of non-dividing yeast cells which exhibit temporal glycolytic oscillations. Oscillations in these variables have the same frequency as oscillations in the activity of intracellular metabolites, suggesting strong coupling between them. These results can be interpreted in light of a recently proposed theoretical formalism in which isentropic thermodynamic systems can display coupled osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…These observations call into question the idea that intracellular water acts as a mere passive biological solvent, as implicitly understood in the standard membrane-based model of the cell. In a subsequent study, we observed that cell volume, heat flux, and temperature also oscillated synchronously with glycolytic oscillations, showing a strong coupling of these physical properties with the biochemical pathway [14]. These results were consistent with a recently proposed thermodynamic formalism where isentropic thermodynamic systems can display coupled oscillations in all extensive and intensive variables, reminiscent of adiabatic waves [16].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…These observations call into question the idea that intracellular water acts as a mere passive biological solvent, as implicitly understood in the standard membrane-based model of the cell. In a subsequent study, we observed that cell volume, heat flux, and temperature also oscillated synchronously with glycolytic oscillations, showing a strong coupling of these physical properties with the biochemical pathway [14]. These results were consistent with a recently proposed thermodynamic formalism where isentropic thermodynamic systems can display coupled oscillations in all extensive and intensive variables, reminiscent of adiabatic waves [16].…”
Section: Introductionsupporting
confidence: 78%
“…They also support the view of the cellular interior as a highly structured and near equilibrium system where energy inputs can be low and sustain regular oscillatory regimes. We argue that all of these experimental results [12,13,14,15], which are difficult to rationalize under the dominant view of the cell, are in line with the association-induction hypothesis (AIH) [17,18,19]. This theory, which still remains unrefuted, offers an alternative conceptual approach based on well-established principles of colloidal physical chemistry to explain how emergent features of the intracellular environment may give rise to cellular function.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Taken together, these observations suggest that conscious awareness—that is, brain interacting with the environment—brings brain dynamics close to a “healthy” equilibrium with some, albeit small, dissipation needed to establish communication channels between cell networks. This situation in brain dynamics being close to equilibrium and of low dissipation may find its parallel in the case of biochemical oscillations; for instance, glycolytic oscillations in cells have been shown to be in near-equilibrium conditions with low dissipation so that small energy inputs can sustain the oscillatory, metabolic regimes (Thoke et al, 2018). These observations challenge the common view of metabolism being highly dissipative, and possibly this notion can be generalized to other biological processes operating in near-equilibrium regimes, like cognition.…”
Section: Probabilistic Description Of Brain Dynamicsmentioning
confidence: 99%
“…One wonders what he would have made of a very recent paper on glycolytic oscillations as a means of maintenance of low entropy in living systems. 142…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%